Numerical Modeling of Material Points Evolution in a System with Gravity (Communications in Computational Physics, 2018)
The evolution of material points interacting via gravitational force in 3Dspace was investigated. At initial moment points with masses of 2.48 Sun masses arerandomly distributed inside a cube with an edge of 5 light-years. The modeling wasconducted at different initial distributions of velocities and different ratios between potentialand kinetic energy of the points. As a result of modeling the time dependenceof velocity distribution function of points was obtained. Dependence of particles fractionwhich had evaporated from initial cluster on time for different initial conditions isobtained. In particular, it was obtained that the fraction of evaporated particles variesbetween 0,45 and 0,63.Mutual diffusion of two classes of particles at different initial conditions in the casewhen at initial moment of time both classes of particles occupy equal parts of cube wasinvestigated.The maximum Lyapunov exponent of the system with different initial conditionswas calculated. The obtained value weakly depends on the ratio between initial kineticand potential energies and amounts approximately 10−5. Corresponding time of theparticle trajectories divergence turned out to be 40-50 thousand years.